Aligning the international protection of 'the public core of the internet' with state sovereignty and national security. Issue 3 (2nd September 2017) - Broeders, Dennis
ABSTRACT: The norm to protect the public core of the internet, originally advocated by the Netherlands Scientific Council for Government Policy, can be operationalised in two ways. Both a layered approach and a functional approach to defining the public core of the internet provide productive ways to discuss safeguarding the functionality and integrity of the core logical and physical infrastructure of the internet from unwarranted state interventions. The article further discusses the tensions between the concept of 'the public core of the internet' and those of state sovereignty and national security. It describes two tiers of objection to the protection of the core internet infrastructure and suggests ways to mitigate them. It concludes that even though there are no easy answers to national security in the cyber age, in the long run, reducing ambiguity in cyberspace will benefit all states. Lifting the public core of the internet out of that ambiguity would be a good starting point.